Effect of TiC/RHA on solid particle erosion of Al6061 hybrid composites fabricated 2 through a 2-step ultrasonic-assisted stir casting process - Balamurugan, K.; Shanmugam, Vigneshwaran; Palani, Geetha; Sundarakannan, R.; Sathish, T.; Linul, Emanoil; Khan, Sher Afghan; Asif, Mohammad (Elsevier Ltd Kidlington Corporate Office, Kidlington, United Kingdom, 2023)
Developing high wear/erosion resistance materials for defense applications is challenging among researchers. The current study investigated the reinforcement effect of Tic and Rice husk ash (RHA) on Al6061 hybrid composites made using a two-step ultrasonic-assisted stir casting process. Four distinct Al6061 hybrid composites were created with varying TiC weight percentages (3, 6, 9, and 12 wt.%). RHA weight percentage was kept constant at 3%. The solid particle erosion test was carried out on each composite using a Taguchi L27 (33) orthogonal array. Experiments were conducted by varying the erodent particle impact angle, erodent velocity, and erodent discharge rate. The effect of each parameter on the erosion rate of the TiC/RHA Al6061 composite was discussed. The composite containing 12% TiC and 3% RHA showed improved erosion resistance. It was found that increasing the TiC addition in the composite resulted in an increase in erosion resistance. SEM images were used to examine the surface failure on the composites caused by erodent impact.